Minorities, their rights, and the monitoring of the European Framework Convention for the Protection of National Minorities : essays in honour of Rainer Hofmann - Hofmann, Rainer, 1953-; Malloy, Tove H.; Caruso, Ugo (Studies in international minority and group rights ;, 2013)
In Minorities, their Rights, and the Monitoring of the European Framework Convention for the Protection of National Minorities Malloy and Caruso offer for the first time a thorough analysis and a knots and bolts description of monitoring of the Convention.